2016
DOI: 10.1021/acs.jproteome.5b00905
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-Array-Based Proteomic Screening of Serum Markers in Systemic Lupus Erythematosus: A Discovery Study

Abstract: A discovery study was carried out where serum samples from 22 systemic lupus erythematosus (SLE) patients and matched healthy controls were hybridized to antibody-coated glass slide arrays that interrogated the level of 274 human proteins. On the basis of these screens, 48 proteins were selected for ELISA-based validation in an independent cohort of 28 SLE patients. Whereas AXL, ferritin, and sTNFRII were significantly elevated in patients with active lupus nephritis (LN) relative to SLE patients who were quie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 76 publications
(145 reference statements)
3
51
0
Order By: Relevance
“…A t ‐test was used if the data passed the D'Agostino‐Pearson normality test; otherwise, the nonparametric Mann‐Whitney U test was used to analyze the data. Likewise, the Pearson's method or nonparametric Spearman's method was used for correlation analyses, as described previously . Tests for multiple comparisons were performed using GraphPad Prism software version 6.…”
Section: Methodsmentioning
confidence: 99%
“…A t ‐test was used if the data passed the D'Agostino‐Pearson normality test; otherwise, the nonparametric Mann‐Whitney U test was used to analyze the data. Likewise, the Pearson's method or nonparametric Spearman's method was used for correlation analyses, as described previously . Tests for multiple comparisons were performed using GraphPad Prism software version 6.…”
Section: Methodsmentioning
confidence: 99%
“…In SLE, IGFBP2, IGFBP4 and IGFBP6 were discovered by array-based proteomic screening as diagnostic biomarkers for lupus (89). Later validation studies using a larger study population confirmed the role of IGFBP2 as a diagnostic biomarker for SLE as well as lupus nephritis (88, 90).…”
Section: Igfbps As Biomarkers In Autoimmune Diseasesmentioning
confidence: 99%
“…The value of the assays has been validated as a means of reducing the need for kidney transplant biopsy and applying biopsy in a more targeted manner. [40] Together, the previous findings have provided solid foundation for future work aimed at improving kidney transplant outcomes through biomarker-guided decisionmaking. [41] The development of novel biomarkers and detection technologies may lead to the creation of multiplex assays, which allows for the measurement of multiple specific biomarkers simultaneously in the same analyte.…”
Section: Prospects and Future Directionsmentioning
confidence: 80%